2022
DOI: 10.3390/healthcare10101812
|View full text |Cite
|
Sign up to set email alerts
|

Customized Deep Learning Classifier for Detection of Acute Lymphoblastic Leukemia Using Blood Smear Images

Abstract: Acute lymphoblastic leukemia (ALL) is a rare type of blood cancer caused due to the overproduction of lymphocytes by the bone marrow in the human body. It is one of the common types of cancer in children, which has a fair chance of being cured. However, this may even occur in adults, and the chances of a cure are slim if diagnosed at a later stage. To aid in the early detection of this deadly disease, an intelligent method to screen the white blood cells is proposed in this study. The proposed intelligent deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Our method offers a full view of a particular site, which enables us to identify the disease, as well as interior areas that have been infected with it. Dermoscopy is the most reliable [ 41 ] and time-effective [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] approach for determining if a lesion is a BCC, MEL, SCC, or MN. A computerized diagnostic approach is required to identify BCC, MEL, SCC, and MN, since the number of confirmed cases of deadly skin cancer is continually growing [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method offers a full view of a particular site, which enables us to identify the disease, as well as interior areas that have been infected with it. Dermoscopy is the most reliable [ 41 ] and time-effective [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] approach for determining if a lesion is a BCC, MEL, SCC, or MN. A computerized diagnostic approach is required to identify BCC, MEL, SCC, and MN, since the number of confirmed cases of deadly skin cancer is continually growing [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…These images were represented by bkl, mel, and nv. Krishnaraj et al [ 52 ] designed machine learning [ 53 , 54 , 55 , 56 ] classifiers that identified binary classes of cervical cancer, such as adenosquamous carcinoma and SCC. They collected the dataset at the University of California, Irvine (UCI) repository, and the Borderline-SMOTE approach was employed to balance the unbalanced data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AI algorithms are being developed and trained to identify patterns and features in medical images, such as X-rays, CT scans, and MRI scans, indicative of various diseases, enabling earlier and more accurate diagnoses. There are many studies related to artificial intelligence in medicine including the articles “AI-Assisted Tuberculosis Detection”, “Classification of Malaria Using Object Detection Models”, “Deep Learning Classifier for Detection of Acute Lymphoblastic Leukemia Using Blood Smear Images”, “Uses of AI in Ultrasound Imaging”, and “Machine Learning in Prostate MRI for Prostate Cancer” [ 31 , 32 , 33 , 34 , 35 ]. The integration of AI into medical imaging is an exciting development that has brought about many changes.…”
Section: Discussionmentioning
confidence: 99%
“…The model achieved an accuracy of 91.1% for diagnosing the C-NMC dataset. Niranjana et al [ 13 ] converted images to HIS color space, segmented WBC cells, then trained the ALLNET model and tested its performance, which achieved an accuracy of 95.54% and a sensitivity of 95.91%. Pradeep et al [ 14 ] used three CNN models to extract image features of an ALL dataset and classify them by RF and SVM.…”
Section: Related Workmentioning
confidence: 99%